Cut back or give it up? The effectiveness of reduce and eliminate appeals and dynamic norm messaging to curb meat consumption. (June 2021) - Sparkman, Gregg; Macdonald, Bobbie N.J.; Caldwell, Krystal D.; Kateman, Brian; Boese, Gregory D.
Abstract: Research has recently started investigating possible methods to encourage consumers to reduce meat consumption. However, few studies examine highly scalable messaging techniques, whether they have long-term effects, and how to best craft such appeals. This includes whether it is more effective to use "reduce" appeals to eat less meat or "eliminate" appeals to categorically stop eating meat. We examine these questions in the context of a recently proposed social psychological technique to curb meat consumption: conveying dynamic norm information that more and more people are starting to curb their meat consumption. In a multi-wave longitudinal survey experiment, we contrast the effectiveness of reduce and eliminate appeals in a scalable medium: an op-ed. We find that the reduce appeal effectively reduced meat consumption in dietary reports five months out from reading the op-ed compared to a control, while the eliminate appeal did not. Further, a second longitudinal experiment assesses the heterogeneity of this effect among a national sample, and finds that these effects exist specifically among populations that are younger, more liberal, more educated, and less wealthy. Highlights: An op-ed using a dynamic norm appeal to reduce meat consumption was effective. A similar op-ed with an appeal to eliminate meat consumption was not effective. Effects of the reduce op-ed lasted for the 5-month duration of the study. Heterogeneity was found in a second study using a nationally representative sample. Effects were found for younger, liberal, more educated, less wealthy participants.